Candidozyma auris Reported in Scotland: a Call for Vigilance Amid Global Rise - M. H. Howe; K. L. Bartie; W. G. Mackay; T. Inkster; S. Cairns; R. Kean; A. M. Bal; G. Ramage (Mycopathologia, 2026)
Candidozyma auris (formerly Candida auris ) is an emerging pathogenic yeast associated with healthcare outbreaks worldwide. Despite increasing reports across Europe, no published data have previously described cases in Scotland. Here, we report the first detections of C. auris in Scotland, as submitted to ARHAI Scotland. Eight cases (seven colonisations, one infection) were identified to date across four NHS Scotland boards, all linked to repatriation or recent hospitalisation abroad. To contextualise these findings, we reviewed publicly available literature and surveillance data for Western and Northern Europe, identifying considerable variation in case numbers and highlighting Scotland’s position among countries with the lowest reported cases. All Scottish cases were imported, underscoring the importance of targeted screening of patients with international healthcare exposure. These findings inform preparedness planning and support recommendations for strengthened surveillance to prevent onward transmission.